2017
DOI: 10.1002/art.40039
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Shows Inflammatory Dysregulation and Tumor‐Like Proliferative Responses in Joints of Patients With Postinfectious Lyme Arthritis

Abstract: Objective Lyme arthritis (LA) is caused by infection with Borrelia burgdorferi and usually resolves following spirochetal killing with antibiotics. However, in some patients, arthritis persists after antibiotic therapy. To provide insights into underlying pathogenic processes associated with post-infectious LA, we analyzed differences in microRNA expression between LA patients with active infection compared with those with post-infectious LA. Methods MicroRNA expression was assayed in synovial fluid (SF) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 53 publications
(93 reference statements)
1
44
0
Order By: Relevance
“…The correlations between gene expression profiles in synovium and previous histologic (Londono et al, ) and microRNA (Lochhead et al, ) findings indicated that microRNA expression and expression of other gene signatures were coregulated. For example, the inflammatory/Th1 signatures in postinfectious LA and the inflammatory RA subtype of RA are accompanied by elevated miR‐155 expression.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The correlations between gene expression profiles in synovium and previous histologic (Londono et al, ) and microRNA (Lochhead et al, ) findings indicated that microRNA expression and expression of other gene signatures were coregulated. For example, the inflammatory/Th1 signatures in postinfectious LA and the inflammatory RA subtype of RA are accompanied by elevated miR‐155 expression.…”
Section: Discussionmentioning
confidence: 71%
“…MicroRNA (miRNA) expression profiling was also conducted previously using RNA collected from the same patients used in this study (Lochhead et al, ). In the previous study, patients with postinfectious LA and those with other forms of chronic inflammatory arthritis had particularly high expression of pro‐inflammatory miR‐155 and low expression of cell‐cycle regulator microRNA let‐7a in synovial tissue, compared with OA tissue.…”
Section: Resultsmentioning
confidence: 99%
“…miRNA expression in patients with postinfectious Lyme arthritis was most similar to the expression in RA patients, where miR‐155, miR‐146a, and miR‐223 were prominent in the synovial fluid, synovial tissue, and synovial fibroblasts . Higher levels of miR‐146a, miR‐17, and miR‐233 are also correlated with increased duration of Lyme arthritis . Thus, the miRNA pattern in SF changes during stages of Lyme arthritis, possibly representing the altering nature of Lyme arthritis after bacterial killing.…”
Section: The Role Of the Innate Immune System During The Early Stagesmentioning
confidence: 71%
“…Elevated levels of miR‐223 and low levels of miRNAs such as miR‐146a, miR‐155, and miR‐142 were found in synovial fluid of Lyme arthritis patients prior to antibiotic therapy (n = 5). Also, elevated levels of white blood cells, specifically PMNs, were found in SF of these patients . In contrast to postantibiotic persistent Lyme arthritis patients (n = 13), who had higher percentages of lymphocytes and mononuclear cells, and a high expression of miR‐146a, miR‐155, miR‐142, miR‐233, and miR‐17‐92.…”
Section: The Role Of the Innate Immune System During The Early Stagesmentioning
confidence: 83%
See 1 more Smart Citation